Sleep in infants with congenital myasthenic syndromes. (November 2017) - Caggiano, Serena; Khirani, Sonia; Verrillo, Elisabetta; Barnerias, Christine; Amaddeo, Alessandro; Gitiaux, Cyril; Thierry, Briac; Desguerre, Isabelle; Cutrera, Renato; Fauroux, Brigitte
Abstract: Background and objectives: Infants with congenital myasthenic syndrome (CMS) are at risk of brief resolved unexplained event (BRUE) and sleep-disordered breathing. The aim of the study was to explore sleep in infants with CMS with a particular focus on heart rate (HR) variability. Methods: Overnight polygraphy was performed and HR variations associated with respiratory events were analysed. Bradycardia and tachycardia were defined as a variation of HR of ±10 bpm from baseline and analysed as events/hour. Results: The data of 5 infants with CMS were analysed. Two patients had known mutations (COLQ and RAPSN). One patient had a tracheostomy. The apnoea-hypopnoea index (AHI) was abnormal in all the patients (range 2.8–47.7 events/h), with the highest AHI being observed in the 3 youngest infants. Nocturnal transcutaneous gas exchange was normal in all patients except the tracheostomised patient. Mean HR was 114 ± 23 bpm with a mean HR index of 4.5 ± 4.3 events/h. The amplitudes of HR variations (bradycardia or tachycardia) were around 15–20 bpm, regardless of the type of respiratory event, and comparable between patients. No correlations were found between HR indexes or variations and the type and mean duration of respiratory events. Ventilatory support was initiated in 3 infants immediately after the sleep study because of a high AHI and/or nocturnal hypoventilation. Conclusions: All 5 infants had an abnormal AHI with younger infants having the highest AHI. Three infants required ventilatory support after the polygraphy, underlining its clinical usefulness. No significant abnormalities of HR were observed during the sleep studies. Highlights: Infants with congenital myasthenic syndromes have sleep-disordered breathing. The youngest infants have the highest apnoea-hypopnoea index. Infants with congenital myasthenic syndromes may require ventilatory support. Heart rate and its variability were normal during sleep.